Influence of High-Performance Composite Sports Equipment on Brand International Sports Marketing Strategy - Xiadi Lyu (Advances in Materials Science and Engineering)
With the continuous development of society, people are paying more attention to sports. In order to make sports brands go to the international market, it is necessary to adopt an international marketing strategy for sports brands. However, due to the late development of most sports brands, the main sports brand market is the mid-to-low-end market. Sports brands have little investment in scientific research and technology and build the market with celebrity endorsements or ultra-low prices. This leads to the lack of an international market for most sports brands, and the sports brands cannot be fully developed. Sports equipment is the core of sports brand marketing, and better quality sports equipment can affect the marketing strategy of sports brands, which improves their international sales capability. High-performance composite sports equipment has many advantages. Compared with traditional sports materials, it has high tensile strength, high wear resistance, and high corrosion resistance. High-performance composite materials were applied to sports equipment and were compared with traditional sports equipment. The quality of the sports equipment, the promotion of the sports brand, the positioning of the sports brand, and the sponsorship of the sports brand were compared between the two sports equipment brands. The test results showed that high-performance composite sports equipment could improve the quality of sports equipment by 25% and had greatly improved sports brand promotion, sports brand positioning, and sports brand sponsorship. Therefore, high-performance composite sports equipment can improve the marketing ability of sports brands in the international market by affecting the quality of sports equipment, promotion of sports brands, positioning of sports brands, and sponsorship of sports brands.